2007
DOI: 10.1002/ijc.22789
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance for familial breast cancer: Differences in outcome according to BRCA mutation status

Abstract: Women with a family history of breast cancer are commonly offered regular clinical or mammographic surveillance from age 30. Data on the efficacy of such programmes are limited. Clinical, pathological and outcome data were recorded on all breast and ovarian cancers diagnosed within familial breast cancer surveillance programmes at collaborating centers in Norway and the UK up to the end of 2005. These have been analyzed according to the mutation status of the affected women (BRCA11ve, BRCA21ve or mutation-nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 31 publications
2
61
0
1
Order By: Relevance
“…[32][33][34][35] Although most studies show a similar prognosis for women with hereditary breast cancers compared with age-matched women with sporadic breast cancers, 34,[36][37][38][39][40] other studies have reported worse survival outcomes. [41][42][43] Despite younger age at presentation, we found that the risk of breast cancer recurrence and death was similar between BRCA carriers and noncarriers in the first 5 years Abbreviations: AT, anthracycline-taxane-containing regimens; BCS, breastconserving surgery; ER, estrogen receptor; HER2, human epidermal growth factor receptor-2; OS, overall survival; pCR, pathologic complete response; PR, progesterone receptor; RFS, recurrence-free survival.…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34][35] Although most studies show a similar prognosis for women with hereditary breast cancers compared with age-matched women with sporadic breast cancers, 34,[36][37][38][39][40] other studies have reported worse survival outcomes. [41][42][43] Despite younger age at presentation, we found that the risk of breast cancer recurrence and death was similar between BRCA carriers and noncarriers in the first 5 years Abbreviations: AT, anthracycline-taxane-containing regimens; BCS, breastconserving surgery; ER, estrogen receptor; HER2, human epidermal growth factor receptor-2; OS, overall survival; pCR, pathologic complete response; PR, progesterone receptor; RFS, recurrence-free survival.…”
Section: Discussionmentioning
confidence: 99%
“…New data suggest that more effective preventive interventions than a simple regular surveillance proposed by the present study 1 for women at increased familial risk of breast cancer are needed for improved outcome. In this study, carriers of BRCA1 mutations fared significantly worse, even when their tumors were diagnosed at an apparently early stage.…”
Section: Dear Sirmentioning
confidence: 84%
“…4 Among 442 patients with a breast cancer diagnosis, BRCA1 carriers had a worse prognosis than BRCA2 carriers and non-BRCA carriers. 1 Although very small number of BRCA2 carriers (n 5 35) and BRCA1 mutation carriers (n 5 89) is subject to biases and errors, the result is to be expected given that most BRCA1 tumors are histopathologically triple negative tumors (ER/PR/HER2 negative) or basal-like subtype 5 in microarray analysis with a worse survival than patients with BRCA2 tumors with a luminal-like subtype (ER-positive). 6 The opposite and unexpected result with better survival for breast cancer patients with BRCA1 than those with BRCA2 mutation is difficult to be explained.…”
Section: Dear Sirmentioning
confidence: 99%
“…An elevated percentage of TNBCs and reduced survival rates are expected for high-risk women, mainly in view of the high susceptibility of BRCA1 mutation carriers to develop cancers of the aggressive basal-like phenotype, frequently associated with hormone receptor negativity, and lack of HER2 overexpression (13)(14)(15)(16). In this context, a number of studies demonstrated the capability of annual multimodal screening programs including magnetic resonance imaging (MRI) to provide an earlier diagnosis of breast cancer in asymptomatic high-risk women (17)(18)(19)(20)(21)(22)(23)(24)(25), leading to expectations for a possible improvement in the outcome of screened high-risk women who are diagnosed with breast cancer.…”
Section: Introductionmentioning
confidence: 99%